DA'WAH THROUGH SOCIAL MEDIA FOR ISLAMIC RELIGIOUS COUNSELLOR AT THE OFFICE OF RELIGIOUS AFFAIR BINUANG DISTRICT POLEWALI MANDAR REGENCY (International Conference on Social and Islamic Studies, 2022)
The purpose of this study was to: (1) find out how the implementation of da'wah through social media for Islamic religious instructors at the Office of Religious Affairs in Binuang District, Polewali Mandar Regency. (2) knowing the supporting and inhibiting factors for the implementation of da'wah through social media for Islamic religious extension agents at the Office of Religious Affairs in Binuang District, Polewali Mandar Regency. This type of research is qualitative research with descriptive data procedures through observation, in-depth interviews, questionnaires and documentation. The results of this study indicate that the implementation of da'wah by Islamic religious instructors at the Office of Religious Affairs of the Binuang District is carried out in two ways, namely, direct da'wah and da'wah through social media. The factors that support the implementation of da'wah on social media include the impact of implementing da'wah on social media that is greater than direct da'wah, besides being more practical in its implementation, congregations on social media are also easier to access information shared as long as they use social media. The inhibiting factors are the still limited knowledge of Islamic religious instructors in the Binuang District about IT (Informatian and Technology), as well as inadequate internet access in several villages in the Binuang District.